Administrative elites and the crisis: what lies ahead for the senior civil service in Greece?. (December 2014) - Spanou, Calliope
The nature of the relationship between the public administration and politics and the subsequent role of the administration appear to be incompatible with the emergence of an administrative elite. After analysing the reasons for this incompatibility, the article explores the impact of the measures taken in the wake of the economic crisis on the civil service and its reform, and also the prospects for the development of a senior civil service. The key, and also the challenge, to any change in this direction remains the rebalancing of the relationship between the public administration and politics. Points for practitioners: What might interest practitioners is the issue of the conditions of effectiveness of civil service reform in times of economic crisis and significant pressure.